The Effect of Music Therapy on Perceived Parental Stress in Perinatal Care: An Exploratory Study. Issue 1 (17th November 2021) - Bollard-Marcovitz, Jenna; Tachdjian, Raffi; Roa, Esteban; Flores, Luisa; Brown, Scott; Gill, Amira; Brown, Chelsea; Wicks, Eiress; Danelyan, Hranush; Tan, Mint; Pak, Grace; Pincus, Bethany; et al.
Abstract: The perinatal experience contains many stressors that can impact parental mental health. We examined the integration of music therapy (MT), an evidence-based health profession, and its stress reduction role in parents during their inpatient maternity and neonatal intensive care unit (NICU) experience. The Perceived Stress Scale (PSS) and Stress Numeric Rating Scale (SNRS-11) were used to measure stress reduction in 34 maternity and NICU parents (17 maternity patients and 17 NICU parents). Participants included parents on the antepartum unit (expecting parents on bedrest), laboring parents, pre-operation parents before cesarean delivery, parents of full-term healthy infants on the postpartum unit, and parents of premature infants on the NICU. Results were calculated based upon number of sessions rather than total number of participants and indicated that after one MT session, a 50% reduction in the SNRS-11 was measured in NICU and antepartum parents. The PSS score demonstrated a more modest stress reduction in the NICU parents but failed to achieve a statistically significant decrease in the maternity group. Findings were in line with existing literature in MT-associated stress reduction levels and may be integrated as part of an ongoing continuity of care during pregnancy, delivery, and NICU hospitalization. Earlier screening for stress may benefit parents during their perinatal hospital stay. Further research exploring the benefits of MT, as part of continuum of care and stress management for the inpatient perinatal parent population, may encourage the inclusion of MT services and improve quality of care.